Profile of Student Ability in Solving Critical Problems in the Concept of Human Physiology - Aulia Rahmah; Yudi Firmanul Arifin; Aminuddin Prahatama Putra (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Learning human physiology is a study that we often encounter in everyday life related to the condition of the body, at any time it can experience problems or abnormalities that result in a decrease in the condition of human health itself. In addition, along with the development of science and technology, more and more problems are encountered in learning human physiology, so that the ability to think is needed in solving existing problems. This study aims to describe the profile of students' abilities in solving critical problems on the concept of human physiology. The study used a descriptive method with a qualitative approach. The data collection instruments in this study included the main instrument, namely the researcher himself and the supporting instrument in the form of a written assignment to describe the profile of students who had programmed human physiology courses. Students are categorized based on a hypothetical theory which contains five levels of critical thinking skills, namely very critical, critical, moderately critical, less critical, and not critical. The results showed that the ability profile of several students of the Biology Education Study Program, Faculty of Teacher Training and Education, Lambung Mangkurat University in solving critical problems on the concept of human physiology. Consists of four levels of critical thinking skills, namely very critical, critical, moderately critical, and less critical.AbstrakPembelajaran fisiologi manusia merupakan kajian yang sering kita jumpai dalam kehidupan sehari-hari yang berhubungan dengan kondisi tubuh, sewaktu-waktu dapat mengalami permasalahan atau kelainan yang berakibat pada menurunnya kondisi kesehatan manusia itu sendiri. Selain itu, seiring dengan perkembangan IPTEK maka semakin banyak pula permasalahan yang dijumpai dalam pembelajaran fisiologi manusia, sehingga diperlukan kemampuan berpikir dalam penyelesaian masalah yang ada. Penelitian ini bertujuan untuk mendeskripsikan profil kemampuan mahasiswa dalam penyelesaian masalah secara kritis pada konsep fisiologi manusia. Penelitian menggunakan metode deskriptif dengan pendekatan kualitatif. Instrumen pengumpulan data pada penelitian ini meliputi instrumen utama yaitu peneliti sendiri dan instrumen pendukung berupa tugas tertulis untuk mendeskripsikan profil mahasiswa yang telah memprogramkan mata kulah fisiologi manusia. Mahasiswa dikategorikan berdasarkan teori hipotetik yangberisi lima tingkatan kemampuan berpikir kritis, yaitu sangat kritis, kritis, cukup kritis, kurang kritis, dan tidak kritis. Hasil penelitian menunjukkan bahwa profil kemampuan beberapa mahasiswa Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkuratdalam penyelesaian masalah secara kritis pada konsep fisiologi manusia. Terdiri dari empat tingkatan kemampuan berpikir kritis yaitu sangat kritis, kritis, cukup kritis, dan kurang kritis.